COVID-19 and Environment: Impacts of a Global Pandemic - Kodera, Sachiko; Rashed, Essam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a reprint of the MDPI IJERPH Special Issue entitled "COVID-19 and Environment: Impacts of a Global Pandemic". The reprint consists of 17 papers with different topics related to the COVID-19 pandemic and environmental impacts using data from different countries all over the globe.